Problem‐based learning in internal medicine: virtual patients or paper‐based problems?. Issue 1 (January 2017) - Sobocan, Monika; Turk, Neja; Dinevski, Dejan; Hojs, Radovan; Pecovnik Balon, Breda
Abstract : Background: Teaching using paper problem‐based learning (p‐PBL) sessions has left some students fatigued with the learning process. Therefore, attempts have been made to replace p‐PBL with digitally enhanced, decision‐making PBL in the form of virtual patients (VP). Student enthusiasm for substituting p‐PBL with VP has not been quantitatively evaluated on the intended educational effects. Aim: To determine the educational effects of substituting p‐PBL sessions with VP on undergraduate medical students in their internal medicine course. Methods: We conducted a randomised controlled study on 34 third‐year undergraduate medical students in the academic year 2015–2016. Student performance after an intervention substituting p‐PBL sessions with VP was analysed. The educational outcomes were measured with knowledge exams and the Diagnostic Thinking Inventory. Results: There was no difference in exam performance between groups ( P  > 0.833) immediately after the intervention, or in long term. Nor was there a significant difference in improvement of diagnostic thinking between groups ( P  > 0.935 and P  > 0.320). Conclusions: Our study showed no significant improvement in diagnostic thinking abilities or knowledge exam results with the use of VP. Educators can add VP to sessions to motivate students, but a significant improvement to educational outcome should not be expected.